Model Aktualisasi “Manusia yang Lahir dari Allah” menurut 1 Yohanes 4:7 di Era Post Truth - Pangaribuan, Rosdinar (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: Humans who are born from God are believers who continuously live in love with God's love. Because living in love is a command that must be actualized by believers as proof that they were born from God and know God. The person who has been born of God (1 John 2:29, 3:9, 5:1) is the person who brings God's love shining into the world. So based on 1 John 4:7 "Man who is born of God" is invited/urged to live a life of love for one another and the basis for a life of love for one another is God's love. Because the essence of a life of loving each other is actually being born from God and knowing God. In the midst of the challenges of the post-truth era that is being faced by society in general and believers in it in particular, the reality of people's lives is that they no longer seek truth but justification, truth is no longer the main thing. So this phenomenon means that people are no longer able to trust each other or even love each other. Ironically, people tend to suspect each other. In this situation, will believers still be able to actualize "Man born of God" according to 1 John 4:7? Abstrak: Manusia yang lahir dari Allah adalah orang percaya yang secara terus menerus hidup saling mengasihi dengan kasih Allah. Oleh karena hidup saling mengasihi merupakan perintah yang harus diaktualisasikan oleh orang percaya sebagai bukti telah lahir dari Allah dan mengenal Allah. Orang yang telah dilahirkan dari Allah (1 Yoh. 2:29, 3:9, 5:1) adalah orang yang membawa kasih Allah bersinar ke dunia. Maka berdasarkan 1 Yohanes 4:7 “Manusia yang lahir dari Allah” diajak/didesak untuk hidup saling mengasihi dan dasar untuk hidup saling mengasihi adalah kasih Allah. Karena sesungguhnya esensi hidup saling mengasihi adalah telah lahir dari Allah dan mengenal Allah. Ditengah tantangan era post truth yang sedang dihadapi oleh masyarakat pada umumnya dan secara khusus orang percaya didalamnya, bahwa realita kehidupan masyarakat yang tidak lagi mencari kebenaran melainkan pembenaran, kebenaran bukan lagi sesuatu yang utama. Sehingga fenomena ini membawa masyarakat tidak lagi mampu saling mempercayai bahkan saling mengasihi. Ironisnya, masyarakat cenderung saling mencurigai satu sama lain. Dalam situasi ini, akankah orang percaya tetap mampu mengaktualisasikan “Manusia yang lahir dari Allah” menurut 1 Yohanes 4:7?